The Role of Dendritic Cells in Adaptive Immune Response Induced by OVA/PDDA Nanoparticles - Daniele R. Pereira; Yunys Pérez-Betancourt; Bianca C. L. F. Távora; Geraldo S. Magalhães; Ana Maria Carmona-Ribeiro; Eliana L. Faquim-Mauro (Vaccines)
Background/Objective: Cationic polymers were shown to assemble with negatively charged proteins yielding nanoparticles (NPs). Poly-diallyl-dimethyl-ammonium chloride (PDDA) combined with ovalbumin (OVA) yielded a stable colloidal dispersion (OVA/PDDA-NPs) eliciting significant anti-OVA immune response. Dendritic cells (DCs), as sentinels of foreign antigens, exert a crucial role in the antigen-specific immune response. Here, we aimed to evaluate the involvement of DCs in the immune response induced by OVA/PDDA. Methods: In vivo experiments were used to assess the ability of OVA/PDDA-NPs to induce anti-OVA antibodies by ELISA, as well as plasma cells and memory B cells using flow cytometry. Additionally, DC migration to draining lymph nodes following OVA/PDDA-NP immunization was evaluated by flow cytometry. In vitro experiments using bone marrow-derived DCs (BM-DCs) were used to analyze the binding and uptake of OVA/PDDA-NPs, DC maturation status, and their antigen-presenting capacity. Results: Our data confirmed the potent effect of OVA/PDDA-NPs inducing anti-OVA IgG1 and IgG2a antibodies with increased CD19+CD138+ plasma cells and CD19+CD38+CD27+ memory cells in immunized mice. OVA/PDDA-NPs induced DC maturation and migration to draining lymph nodes. The in vitro results showed higher binding and the uptake of OVA/PDDA-NPs by BM-DCs. In addition, the NPs were able to induce the upregulation of costimulatory and MHC-II molecules on DCs, as well as TNF-α and IL-12 production. Higher OVA-specific T cell proliferation was promoted by BM-DCs incubated with OVA/PDDA-NPs. Conclusions: The data showed the central role of DCs in the induction of antigen-specific immune response by OVA-PDDA-NPs, thus proving that these NPs are a potent adjuvant for subunit vaccine design.